2019
DOI: 10.1093/mnras/stz3076
|View full text |Cite
|
Sign up to set email alerts
|

Obscuration properties of mid-IR-selected AGN

Abstract: The goal of this work is to study the obscuration properties of mid-infrared (mid-IR) selected AGN. For that purpose, we use WISE sources in the Stripe 82-XMM area to identify mid-IR AGN candidates, applying the Assef et al. criteria. Stripe 82 has optical photometry ≈ 2 times deeper than any single-epoch SDSS region. XMM-Newton observations cover ∼26 deg 2 . Applying the aforementioned criteria, 1946 IR AGN are selected. ∼ 78% have SDSS detection, while 1/3 of them is detected in X-rays, at a flux limit of ∼ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Our analysis of XMMFITCAT-Z sources is consistent with many previous studies (Eckart et al 2010;Stern et al 2012;Assef et al 2013;Yan et al 2013;Mateos et al 2012Mateos et al , 2013Mountrichas et al 2017bMountrichas et al , 2020Pouliasis et al 2020) showing that MIR diagnostics are powerful for the identification of luminous AGN, but they fail for AGN with lower luminosity and/or mild absorption, where the stellar contribution to the optical/MIR emission is non-negligible. By focusing on the X-ray properties, we can identify these objects.…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis of XMMFITCAT-Z sources is consistent with many previous studies (Eckart et al 2010;Stern et al 2012;Assef et al 2013;Yan et al 2013;Mateos et al 2012Mateos et al , 2013Mountrichas et al 2017bMountrichas et al , 2020Pouliasis et al 2020) showing that MIR diagnostics are powerful for the identification of luminous AGN, but they fail for AGN with lower luminosity and/or mild absorption, where the stellar contribution to the optical/MIR emission is non-negligible. By focusing on the X-ray properties, we can identify these objects.…”
Section: Discussionsupporting
confidence: 91%
“…Although these colour criteria are very efficient in uncovering obscured AGN selected in the mid-IR, X-rays are known to miss a large fraction of obscured sources selected based on optical-IR colours. Mountrichas et al (2020) used sources detected in Stripe 82 and found that among IR selected AGN with an SDSS detection, 43% are optically red. However, this percentage drops to 23% among those AGN that are also X-ray detected.…”
Section: Effectiveness Of Optical / Mid-ir Colours In Classifying X-r...mentioning
confidence: 99%
“…Although these colour criteria are very efficient in uncovering obscured AGN selected in the mid-IR, X-rays are known to miss a large fraction of obscured sources selected based on optical/mid-IR colours. Mountrichas et al (2020) used sources detected in Stripe 82 and found that among IR selected AGN with SDSS detection, 43% are optically red. However, this percentage drops to 23% among those AGN that are also X-ray detected.…”
Section: Effectiveness Of Optical / Mid-ir Colours In Classifying X-r...mentioning
confidence: 99%